Landscapes of conversion: the evolution of the residential school sites at Wiikwemkoong and Spanish, Ontario - Harvey, Jennifer N. (Laurentian University of Sudbury, 2019)
This thesis explores the history of the Society of Jesus and its efforts at missionary work from the 17th century in New France to the 20th century in Canada and the use of architecture and landscape development to settle and convert Indigenous peoples into Euro-Christian communities. The Jesuits focused on using Indigenous children to aid in the conversion of Indigenous societies and their efforts resulted in the residential school complexes of the 19th and 20th century in the villages of Wiikwemkoong and Spanish, Ontario. Using illustrations, photographs and written descriptions of former student experiences the atmosphere of the physical environments in Spanish are depicted. The ambitious land and architecture strategies of the Society contributed to the failure of the Spanish Indian Residential Schools. The thesis concludes with a discussion regarding the former sites of the Jesuit residential schools in Northern Ontario and the current discourse on Canadian residential school buildings and sites in the media. Master of Arts (MA) in Humanities